2021
DOI: 10.1007/s00167-021-06572-1
|View full text |Cite
|
Sign up to set email alerts
|

Remnant preserving ACL reconstruction with a functional remnant is related to improved laxity but not to improved clinical outcomes in comparison to a nonfunctional remnant

Abstract: Purpose The Anterior cruciate ligament (ACL) remnant has been pointed out as a ligamentization enhancer. Nonetheless, the remaining tissue can be functional if it still provides some stability or nonfunctional. This study intends to compare the clinical results and knee stability of functional vs. nonfunctional remnant preservation ACL reconstruction (ACLR). Methods One hundred and seventy-ive patients with ACL injuries were included and underwent remnant preservation ACLR. They were divided into two groups ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 70 publications
(171 reference statements)
0
17
0
Order By: Relevance
“…The results showed that preservation without remnant tensioning had significant advantages in terms of Lysholm score, IKDC grade, Pivot-shift test and side-to-side difference, but group preservation with remnant tensioning does not show the significant superiority, comparing to Group ACLR-S. The results may be due to the points mentioned above, the differences in ACLR procedures, remnant placement, and amount and quality of remnant preservation ( 33 , 40 , 48 , 49 ).…”
Section: Discussionmentioning
confidence: 94%
“…The results showed that preservation without remnant tensioning had significant advantages in terms of Lysholm score, IKDC grade, Pivot-shift test and side-to-side difference, but group preservation with remnant tensioning does not show the significant superiority, comparing to Group ACLR-S. The results may be due to the points mentioned above, the differences in ACLR procedures, remnant placement, and amount and quality of remnant preservation ( 33 , 40 , 48 , 49 ).…”
Section: Discussionmentioning
confidence: 94%
“…In ACL reconstruction surgery, the importance of surgical planning is supported by the evidence that up to 8.2% of ACLR end in graft failure [7, 9, 11, 19, 22, 29, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, remnant preservation is commonly performed by passing the grafted tendon through the remnant [8, 11, 17, 19, 26, 34, 37]. Some studies indicated that only tibial tunnel enlargement of single‐bundle ACLR, and only AM bundle tunnel enlargement were reduced by the conventional remnant preservation technique [17, 31, 34, 37].…”
Section: Discussionmentioning
confidence: 99%